Institutional processes in the Muslim Umma of Ukraine - Aristova, A. (Ukrai͏̈ns'ke relihijeznavstvo, 2013)
In Ukraine, there are now officially registered six All-Ukrainian Muslim departments and centers, a number of Islamic-based public and political organizations, associations of national minorities, the Islamic lands dominated by Islamic religion. The Islamic community of the country is replenished annually by migrants and students from countries of different Islamic orientation. It is clear that all this actualizes the problem of inter-institutional relations in the Islam of Ukraine, the search for ways and means of minimizing and preventing possible confrontations and conflicts between them.